(3OQGSI aj GdbGfhf GdebGQfs - (3fYje(B, (3eZHZHs (((3Oe(B):s ((3Of(B)(3,s, 2005)
(3jVe eaghe LQe JHjV GdCehGd, eaghe GdCehGd ZjQ GdeTQhYI, eaghe GdCTNGU GdeTHhgjf, YfGUQ LQe JHjV GdCehGd, OhQ GdeDSSGJ aj JHjV GdCehGd, eDSSGJ GdUjQaI, GdTQcGJ GdeGdjI hGdhSGWI GdeGdjI, gjFGJ GdESJKeGQ GdLeGYj, GdYbhO GdEFJeGfjI, GdEjLGQ GdJehjdj, MSGH Gdbje GdefbhdI hGdMSGH GdeTJQc, eDSSGJ ZjQ GdNGVYI ddSQjI, eUGOQ LQe JHjV GdCehGd, GdeHQQGJ GdTQYjI dJgQjH GdCehGd, GdSLf hGdZQGeI, bGfhf ecGaMI JHjV GdCehGd aj ShjSQG s
(3HHdjhZQGajG(B: (3U(B.429s
Keywords: (3GdJRhjQs; (3LQGFe GdCehGds; (3LQGFe GdJgQjHs